El Estado “democrático” y la “democratización” de los Estados - Alshboul, Ayman (Nómadas. Critical Journal of Social and Juridical Sciences, 2007)
The growing fight of the “democratic” states to democratize the underdeveloped countries comes to opining a new era of colonialism that, without a doubt, it has caused big cultural invasions in against the will of many nations of the planet. This article analyze the democracy imposed by the economic powers on the states of the third world with the purpose of creating bordering countries that work as guardians of their interests.